Large-Signal Nonlinear Average Model for a Voltage-Controlled Flyback Converter - David Eduardo Giraldo-Hernández; Mario Andrés Bolaños-Navarrete; Fabiola Angulo; Gustavo Osorio; Nicols Astaiza; Juan David Mina-Casaran; Wilder Herrera (Energies)
Flyback converters are popular in various electronic applications due to their efficiency, galvanic isolation, and voltage stepping-up. However, their modeling and analysis present significant challenges. Traditional switched models offer high precision but require extensive computational resources, which is impractical for large-scale simulations. The alternative linear large-signal models are effective for studying stability near fixed operating points but fall short in capturing transient dynamics, limiting their use in the analysis and design of large or complex systems. This paper presents a novel nonlinear approach for representing a proportional–integral (PI) voltage-controlled flyback converter operating in continuous conduction mode (CCM) that accurately captures transients while reducing the computational burden. Numerical simulations in a study case confirm that the model effectively captures the converter dynamics under various conditions, achieving steady-state errors below 0.07% and accelerations up to 54×. These results facilitate efficient design iterations across a broad range of applications, including renewable energy systems, battery charging, and electric vehicles.